The potential effects of climate change on the habitat range of the Vancouver Island marmot (Marmota vancouverensis). (30th March 2018) - Thelin, Larissa; Lewis, Jeff; Gilchrist, Alan; Craig, Jessica
Abstract: Research shows that the rise in surface temperatures induced by climate change will cause many animal species to follow their shifting ranges either upwards in elevation or polewards. Since the Vancouver Island marmot, one of Canada's most vulnerable species, is found in only a few fragmented locations on the Island, a shift in range could be detrimental to their well‐being. Using habitat restrictions based on existing successful hibernacula, this study modeled the marmot's current potential habitat range, which was found to be approximately 3200 km 2, or 9.6% of the area of Vancouver Island. Next, we modeled the potential shift in habitat range due to the projected change in the climate of Vancouver Island and found that the habitat range shrinks to just 85 km 2, or 0.2% of Vancouver Island. These results outline a clear trend in marmot habitat—that the impacts of climate change will substantially reduce the amount of potential habitat for the Vancouver Island marmot. We recommend that further research focus on the impacts of climate change on local climate regimes, including snowpack, marmot predators, and marmot food sources. Soil depths and natural meadows are also important to marmot habitat and require additional research and mapping. Key Messages: Vancouver Island marmot habitat is insular and highly susceptible to changes in climate. Based on ClimateBC projections, this study finds that the habitat range of the Vancouver Island marmot will shrink by approximately 97% by the year 2080. Further research is required to determine the full extent to which the vulnerable Vancouver Island marmot will be negatively influenced by climate change.